Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content:• Future scenarios for teaching mathematical applications in artificial intelligence (robots as a model) at the secondary level in the Kingdom of Saudi ArabiaDr. Norah Shabeeb AboJalbah, Prof. Ghalya Hamad Al-Sulim• Exploring the Effect of Equitable Teaching Strategy on Perseverance in Solving Mathematical Problems: A Qualitative StudyMr. Mohammed Nejer Alotaibi , Prof. Mohammed Sanat Alharbi• Effectiveness of Using the Google Classroom Platform on Achievement and Motivation  Toward Learning Science Among Eighth Grade Students in Palestine 1948Ms. Rofaida Salah Khamaise, Ms. Bothaina Soliman Khatib• The effect of using the project-based learning (pbl) strategy on female student attitudes  towards the subject of Physical educationDr. Maha Ahmad Alawrtani• The Use of Blended Learning and Its Impact on Developing Graduate Students’ Attitudes  at King Abdulaziz University Toward Self-Directed LearningMs. Nada Murizaq Al-Sulami• Professional Development of English Language Teachers in the Kingdom of Saudi Arabia  in Light of the South Korean Experience: A Comparative StudyMs. Hind Marzouq Almutairi, Co-Prof. Tahani Khalid Al-Jubair
Keywords: Journal of Curriculum and Teaching Methodology